(untitled) (Research, Society and Development, 2021)
This research aimed to analyze how to commercialize agricultural products in the urban micro-region of São Luís, in the state of Maranhão. For the study, family farmers and consumers of horticultural products and foods sold in distribution centers in the region of São Luís, in the state of Maranhão, were chosen as target audience. For this, bibliographic and documentary research was carried out, in addition to field research, in which research, interviews were used, as well as direct verification in the collection of data used in the analyzes carried out. With the conclusion of the research, it was found that from the theoretical and empirical approaches developed in the study, the objective has been achieved within the proposed and not probabilistic study proposal. In this approach, the research considered, as a basic element, the importance of small producers and family farming in food production in the São Luís shopping center, in addition to serving the consumer market in the study region, thus aligning the analysis and discussion results to the dimensions of development proposed by the research. It is worth noting that, in the commercialization process, for example, it was verified, among other characteristics, the use of proper transport for the transfer of the goods to the commercialization centers, in packages without identification of the name of the producer, a fact that could be present collaborate for the logistics and dissemination of the products offered. However, it is worth mentioning that the non-disclosure of brands and packaging is not a relevant element in the marketing of products, as it was found that local consumers, in general, trust in the origin and quality of products offered by marketing centers - such as CEASAs .